Continuation of exercise is necessary to inhibit high fat diet-induced β-amyloid deposition and memory deficit in amyloid precursor protein transgenic mice. - Masato Maesako; Kengo Uemura; Ayana Iwata; Masakazu Kubota; Kiwamu Watanabe; Maiko Uemura; Yasuha Noda; Megumi Asada-Utsugi; Takeshi Kihara; Ryosuke Takahashi; Shun Shimohama; Ayae Kinoshita (PLoS ONE, 2013)
High fat diet (HFD) is prevalent in many modern societies and HFD-induced metabolic condition is a growing concern worldwide. It has been previously reported that HFD clearly worsens cognitive function in amyloid precursor protein (APP) transgenic mice. On the other hand, we have demonstrated that voluntary exercise in an enriched environment is an effective intervention to rescue HFD-induced β-amyloid (Aβ) deposition and memory deficit. However, it had been unclear whether consumption of HFD after exercising abolished the beneficial effect of exercise on the inhibition of Alzheimer's disease (AD) pathology. To examine this question, we exposed wild type (WT) and APP mice fed with HFD to exercise conditions at different time periods. In our previous experiment, we gave HFD to mice for 20 weeks and subjected them to exercise during weeks 10-20. In the present study, mice were subjected to exercise conditions during weeks 0-10 or weeks 5-15 while being on HFD. Interestingly, we found that the effect of exercise during weeks 0-10 or weeks 5-15 on memory function was not abolished in WT mice even if they kept having HFD after finishing exercise. However, in APP transgenic mice, HFD clearly disrupted the effect of exercise during weeks 0-10 or weeks 5-15 on memory function. Importantly, we observed that the level of Aβ oligomer was significantly elevated in the APP mice that exercised during weeks 0-10: this might have been caused by the up-regulation of Aβ production. These results provide solid evidence that continuation of exercise is necessary to rescue HFD-induced aggravation of cognitive decline in the pathological setting of AD.